Assessment of ecological stability of the built environment in relation to sustainable construction - Junakova Natalia; Junak Jozef; Šelingova Eva (Selected Scientific Papers: Journal of Civil Engineering, 2019)
When placing buildings in a landscape environment, the urban and architectural design of the building must be in harmony with the surrounding environment. The environmental criterion in assessing the sustainability of buildings and the subsequent environmental certification of buildings is the construction site selection in terms of its ecological importance. The way to determine the ecological value of a territory is through the determination of the landscape’s ecological stability, which can be considered as a basis for assessing all conditions and assumptions of land use. Maintaining ecological stability on Earth is a prerequisite for sustainable development and is of long-term strategic importance for the development of society.